La forêt comme inspiration et image-outil de coconception - Marina Khémis (Projets de Paysage)
The article addresses the subject of the forest through an approach combining architecture, landscape, scenography, and programming. In particular, it focuses on how a cultural reference, a symbol and an image - in this case that of the forest - served as a source of inspiration and as a co-designing tool in the creation of a cultural space : the Swedish pavilion for Expo 2020 in Dubai. The aim is to explore the process of creating a sensory and semantic experience that uses the aesthetic and symbolic potential of the forest on different levels and as an architectural construct which is not intended to imitate the forest but to provide something to be experienced and felt.